2013
DOI: 10.4081/ejh.2013.e3
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory effects of exercise training promote atherosclerotic plaque stabilization in apolipoprotein E knockout mice with diabetic atherosclerosis

Abstract: Physical exercise is the cornerstone of cardiovascular disease treatment. The present study investigated whether exercise training affects atherosclerotic plaque composition through the modification of inflammatoryrelated pathways in apolipoprotein E knockout (apoE−/−) mice with diabetic atherosclerosis. Forty-five male apoE−/− mice were randomized into three equivalent (n=15) groups: control (CO), sedentary (SED), and exercise (EX). Diabetes was induced by streptozotocin administration. High-fat diet was admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
3
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 48 publications
(49 reference statements)
3
34
3
5
Order By: Relevance
“…In nondiabetic Apoe knockout mice, exercise decreased plasma MMP‐9 (degrades collagen, found in macrophages in plaques) and increased TIMP‐1 (inhibits MMP‐2, MMP‐9) while increasing collagen and elastin content of plaques and decreasing plaque size . Consistent with this report, recent reports also indicated that exercise reduces MMPs and increases TIMP‐1, elastin, and collagen levels in the plaque and thereby confers plaque stability and a reduction in lesion incidence and arterial stenosis . All of these improvements correlate with reduction in macrophages in the plaques, implying that exercise can prevent foam cell formation and reduced macrophage motility, the hallmarks of atherogenesis.…”
Section: Role Of Exercisesupporting
confidence: 79%
See 3 more Smart Citations
“…In nondiabetic Apoe knockout mice, exercise decreased plasma MMP‐9 (degrades collagen, found in macrophages in plaques) and increased TIMP‐1 (inhibits MMP‐2, MMP‐9) while increasing collagen and elastin content of plaques and decreasing plaque size . Consistent with this report, recent reports also indicated that exercise reduces MMPs and increases TIMP‐1, elastin, and collagen levels in the plaque and thereby confers plaque stability and a reduction in lesion incidence and arterial stenosis . All of these improvements correlate with reduction in macrophages in the plaques, implying that exercise can prevent foam cell formation and reduced macrophage motility, the hallmarks of atherogenesis.…”
Section: Role Of Exercisesupporting
confidence: 79%
“…In ApoE knockout diabetic mice, exercise decreases MMP‐2 (degrades collagen, found in SMCs in plaques), MMP‐3 (degrades type II collagen, found in SMCs and macrophages in plaque), and MMP‐8 (degrades collagens, found in macrophages in plaque) levels as well as IL‐6 (expressed by M1 macrophages). Collagen, elastin, and TIMP‐2 (inhibitor of MMP‐2 and MMP‐9) were also increased in parallel with fibrous cap thickness and fewer . In nondiabetic Apoe knockout mice, exercise decreased plasma MMP‐9 (degrades collagen, found in macrophages in plaques) and increased TIMP‐1 (inhibits MMP‐2, MMP‐9) while increasing collagen and elastin content of plaques and decreasing plaque size .…”
Section: Role Of Exercisementioning
confidence: 98%
See 2 more Smart Citations
“…Previous work has confirmed a relationship between dietary flavonoid intake and incidence of diabetes (Bahadoran et al, 2013;Kadoglou et al, 2013); however, to our knowledge, we are the first to show the relationship between flavonoid intake on markers of diabetes severity and retinopathy in U.S. adults with diabetes. Not only was HFVC an independent predictor of diabetes-related biomarkers, but for each 10 U increase in HFVC index, participants had 33% lower odds to have retinopathy.…”
Section: Discussionmentioning
confidence: 47%